Pengembangan Modul Interaktif Pada Mata Pelajaran IPA Terpadu Kelas VIII - Kuswanto, Joko (UNIVED Press, 2019)
One form of interactive teaching material is an interactive module. Interactive modules are a type of planned learning activity unit, designed to help individual students achieve their learning goals. This research aims to develop an interactive module for the Class VIII Integrated Science subject. The research method used is development research with stages of design, production, evaluation, and analyzing data with percentages. The results of this research indicate that learning media in the form of interactive modules developed for the Class VIII Integrated Science subject are suitable for use in learning by teachers and students. Based on several stages of testing, the interactive module is categorized as valid with a feasibility level of 82% with good criteria. It is hoped that this research can become a learning medium for Class VIII Integrated Science subjects and can be useful for teachers, students and advanced researchers.